An unacknowledged harmony : philo-Semitism and the survival of European Jewry - Edelstein, Alan (Contributions in ethnic studies, 1982)
Introduction -- Toward a definition of Philo-Semitism -- Philo-Semitism in the Middle Ages I -- Philo-Semitism in the Middle Ages II - Jewish emancipation I -- Jewish emancipation II -- Toward an understanding of Philo-Semitism -- Conclusions.